Critical Review on the Unique Interactions and Electroanalytical Challenges Related to Cathodes ‐ Solutions Interfaces in Non‐Aqueous Mg Battery Prototypes. Issue 17 (26th June 2021) - Attias, Ran; Sharon, Daniel; Goffer, Yosef; Aurbach, Doron
Abstract: Rechargeable batteries based on Mg metal anodes may be a promising alternative to current Li‐ion battery systems. However, the development of practical rechargeable Mg batteries (RMBs) is hindered by the absence of cathode materials that can reversibly intercalate Mg ions with a reasonably fast kinetic, while still exhibiting high capacity and high working voltages. In this minireview we summarize our recent progress in understanding cathodes/electrolyte solutions interfaces in non‐aqueous Mg systems. While most studies in the field of cathode materials for RMBs focus on the solid‐state diffusion phenomena of the bare Mg ion within the solid hosts, this minireview summarizes several important findings that demonstrate how the electrochemical response of the cathode material is also significantly influenced by the solution chemistry and structure. We provide a comprehensive description of the sequential steps taking place in the electrochemical intercalation reactions, with an emphasis on the charge transfer process across the solution/electrode interfaces. We discuss the different manner in which the electrolyte solutions′ chemical characteristics can impact each step of the intercalation process and why this information is important for the development of new cathode materials for rechargeable Mg batteries. We believe that these types of fundamental investigations are crucial steps for the realization of this interesting battery technology. Abstract : Solution chemistry and structure: The studies presented in this mini review deals with important questions related to electrolyte solution/cathode interfaces and the influence of the electrolyte solutions chemistry on the electroanalytical response of magnesium ions intercalation compounds. These studies clearly demonstrate that the electrolyte solutions chemistry affects the intercalation process in terms of thermodynamic, kinetics, RDS, and heterogeneous rate constant for charge transfer across the electrodes' interfaces.